2016
DOI: 10.1097/bpb.0000000000000219
|View full text |Cite
|
Sign up to set email alerts
|

Use of glenoid inclination angle for the assessment of unilateral congenital high scapula

Abstract: Little has been reported on the motion of the scapula in Sprengel's deformity. Fourteen patients with unilateral congenital high scapula underwent the Woodward procedure from 1986 to 2004. The median age of the patients at the time of surgery was 4.4 years and the median follow-up duration was 8.8 years. The range of motion of the shoulder and the glenoid inclination angle (GIA) were measured preoperatively and at the final visit. The range of motion of the shoulder and GIA improved at the final visit. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The exception to this is the GIA (Fig. 1), which was initially described by Nakamura et al 20 In a series of 14 shoulders, the authors found a moderate positive correlation between the GIA and shoulder abduction range. Our results based on 58 shoulders appear to corroborate this finding, albeit with a slightly weaker correlation (r ¼ 0.41, Fig.…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…The exception to this is the GIA (Fig. 1), which was initially described by Nakamura et al 20 In a series of 14 shoulders, the authors found a moderate positive correlation between the GIA and shoulder abduction range. Our results based on 58 shoulders appear to corroborate this finding, albeit with a slightly weaker correlation (r ¼ 0.41, Fig.…”
Section: Discussionmentioning
confidence: 77%
“…Numerous radiographic markers have been described for Sprengel's deformity. 1,7,19,20,23,28 In almost all cases, the radiographic markers were used to compare scapular position change from before and after surgery, but had not been correlated with shoulder function or clinical relevance. The exception to this is the GIA (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations